Ascertaining the facts in disciplinary procedures which are initiated against convicts during the serving of a prison sentence - drakić, dragiša; Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Summary: The rights and obligations of convicts while serving prison sentences in „penitentiary“ are regulated by strict rules. Every failure to comply with the law and bylaws is grounds for disciplinary responsibility of the convict, which also means that in the end disciplinary measures will be ordered. For a disciplinary measure to be ordered against the convict, it is necessary to ascertain the truth – that the convict has broken the rules of behavior while serving his prison sentence. To ascertain the truth in a disciplinary procedure in a penitentiary, based on current regulation, is an extremely difficult task for the disciplinary commission, the prison warden or the operating judge. In this work the authors point out the difficulties of ascertaining the truth in disciplinary procedures against convicts in a „penitentiary“ because of the existence of „doubt“ whether he has committed a serious or mild disciplinary offence. Key words: truth, offence, procedure, judge, commission, warden.